2000
DOI: 10.1038/77139
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-regulated association of RAD50/MRE11/NBS1 with TRF2 and human telomeres

Abstract: Telomeres allow cells to distinguish natural chromosome ends from damaged DNA and protect the ends from degradation and fusion. In human cells, telomere protection depends on the TTAGGG repeat binding factor, TRF2 (refs 1-4), which has been proposed to remodel telomeres into large duplex loops (t-loops). Here we show by nanoelectrospray tandem mass spectrometry that RAD50 protein is present in TRF2 immunocomplexes. Protein blotting showed that a small fraction of RAD50, MRE11 and the third component of the MRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
398
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 548 publications
(415 citation statements)
references
References 31 publications
14
398
1
2
Order By: Relevance
“…Despite this concentration constancy we observed a cell cycle dependent relocation for both proteins. Immunostainings have shown that TRF2 and TRF1 are present at the telomeres throughout the cell cycle (21,60). We have now added quantitative data to these observations based on GFP-constructs and single cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this concentration constancy we observed a cell cycle dependent relocation for both proteins. Immunostainings have shown that TRF2 and TRF1 are present at the telomeres throughout the cell cycle (21,60). We have now added quantitative data to these observations based on GFP-constructs and single cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…RAD50, MRE11 and NBS1 are present in TRF2 immunocomplexes (Zhu et al, 2000) via their interaction with RAP1 (O'Connor et al, 2004). RAD50 and MRE11 are located at telomeres throughout interphase, and are joined by NBS1 in S-phase (Zhu et al, 2000). It has been suggested that MRE11 and RAD50 may be required to stabilize telomere (t)-loop formation (which is essentially an unresolved homologous recombination event) throughout most of the cell cycle, and that the transient recruitment of NBS1 in Sphase may be required for access of the DNA replication machinery (Zhu et al, 2000).…”
Section: Screen For Alt Genes W-q Jiang Et Almentioning
confidence: 97%
“…In addition to being present in APBs, the MRN complex has been shown to be associated with telomeres (Zhu et al, 2000). RAD50, MRE11 and NBS1 are present in TRF2 immunocomplexes (Zhu et al, 2000) via their interaction with RAP1 (O'Connor et al, 2004).…”
Section: Screen For Alt Genes W-q Jiang Et Almentioning
confidence: 99%
See 2 more Smart Citations